2008
DOI: 10.1021/jp709651n
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Reactivity of the Tetrahedrally Coordinated High-Valence d0 Transition Metal Oxides toward the C−H Bond Activation of Alkanes:  A Cluster Model Study

Abstract: We have carried out a theoretical study on the structure-function relationship for the selective oxidation of lower alkanes (C1-C4). The H abstraction mechanism has been examined over the model catalysts of high-valence d0 transition metal oxides in the tetrahedral coordination. The intrinsic connections among the H abstraction barrier, the strengths of the O-H and the M-O bonds, the ability of electron transfer, as well as the energy gap of frontier orbitals of the oxides have been rationalized in terms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 47 publications
1
26
0
1
Order By: Relevance
“…Extensive studies have concluded that the initial methylene CAH bond breaking is the rate-determining step in the propane oxidation reaction, and the surface V 5+ @O site is generally considered to be the active center [51][52][53][54][55]. In the case of 3%VTe z O x -MS catalysts, vanadium species existed predominantly as tetrahedral V 5+ sites with a terminal V@O bond.…”
Section: Correlation Between Catalyst Structure and Catalytic Performmentioning
confidence: 99%
“…Extensive studies have concluded that the initial methylene CAH bond breaking is the rate-determining step in the propane oxidation reaction, and the surface V 5+ @O site is generally considered to be the active center [51][52][53][54][55]. In the case of 3%VTe z O x -MS catalysts, vanadium species existed predominantly as tetrahedral V 5+ sites with a terminal V@O bond.…”
Section: Correlation Between Catalyst Structure and Catalytic Performmentioning
confidence: 99%
“…Hydrogen affinity (E " ) has previously been shown to be a suitable descriptor of reactivity for radical hydrocarbon activation [23][24][25] . However, these analyses have traditionally been limited to trends within groups of certain transition metal oxides.…”
mentioning
confidence: 99%
“…Traditionally, most of the reported descriptor approaches have been limited to describing one reaction within a single class of catalyst materials 2,[23][24][25][26] . In this work, we have shown that hydrocarbon activation provides a unique opportunity for the development of a universal scaling relationship that accurately describes a vast library of catalyst materials and reactions, which has not been previously demonstrated.…”
mentioning
confidence: 99%
“…Hydrogen affinity or hydrogen adsorption energy (E H ), defined as the energy difference between hydrogenated and bare active sites, is an activity descriptor for CH bond activation on transition metal oxides that undergoes radical-like transition states. [67,68] Nørskov and co-workers further demonstrated that E H is a universal descriptor for predicting CH activation barriers of methane over a wide range of catalysts that proceed via similar radical transition states. [69] Their calculations covered certain types of metals, metal oxides, metal-exchanged zeolites, metal-organic frameworks (MOFs), and metal-embedded graphene.…”
Section: Activity Descriptor For the Dehydrogenation Mechanismmentioning
confidence: 99%